2012
DOI: 10.1002/jsc.1900
|View full text |Cite
|
Sign up to set email alerts
|

The internationalization process of Chinese SMEs: does globalizing wholesale markets play a role?

Abstract: Child J, Rodrigues SB. 2005. Th e internationalization of Chinese fi rms: a case for theoretical extension? Management and Organization Review 1(3): 381-410.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…It conducted an analysis of profitability patterns across the commodity trading market, which suggested that purchasers responded positively to co-location of booths engaged in the same type of commodity because it enabled them to compare prices easily and conveniently. In turn this stimulated competition which drove down prices and attracted more clients (Wang and Ngoasong, 2012). As a result of these findings, the Administrative Bureau on.…”
Section: Classifying the Commodities By Industry Within The Same Distmentioning
confidence: 96%
See 2 more Smart Citations
“…It conducted an analysis of profitability patterns across the commodity trading market, which suggested that purchasers responded positively to co-location of booths engaged in the same type of commodity because it enabled them to compare prices easily and conveniently. In turn this stimulated competition which drove down prices and attracted more clients (Wang and Ngoasong, 2012). As a result of these findings, the Administrative Bureau on.…”
Section: Classifying the Commodities By Industry Within The Same Distmentioning
confidence: 96%
“…In 1992 it adopted the development strategies of 'Encouraging Industry with Commerce' and 'Correlating Manufacturing and Trade' to encourage the booth-keepers to transform commercial capital into industrial capital (Wang and Ngoasong, 2012). Meanwhile, it launched various incentive schemes to promote industrial development (Table 4) The globalisation of Yiwu Commodity Trading Market and its region has been attributed to various incentive schemes to develop the export-oriented economy adopted by Yiwu Municipal Government (Table 5).…”
Section: Emergence and Formation Of Industrial Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, due to the imparity of distribution of financial resources, there is greater demand for credit from the poor or near‐poor population than from richer people. Small and medium private enterprises are notable entities in this general demand (Wang and Ngoasong, 2012). In many cases, the credits going to small and medium‐sized enterprises (SMEs) are also treated as microfinance.…”
Section: Introductionmentioning
confidence: 99%
“…While most studies focus on raising export figures of China (see e.g. [1]), also import figures increased during the last years. Looking at specific commodities, the enormous potential of the Chinese market emerges (see figure 1).…”
Section: Introductionmentioning
confidence: 99%